Genetic Variability in Ginger (Zingiber officinale Rosc.) - Dev, H.; Sharma, Vipin (International Journal of Bio-resource and Stress Management, 2022)
The present investigations were carried out at the Experimental Farm of the Department of Vegetable Science, Dr. YS Parmar University of Horticulture and Forestry, Nauni, Solan (HP) during kharif season (April–November), 2011. The objective of the study was to assess the genetic variability of 40 diverse genotypes of ginger collected from different parts of the country including one recommended variety Himgiri as check. These genotypes had shown considerable variability for all the parameters studied. The observations were recorded on emergence, number of tillers and leaves plant-1, leaf length and breadth, plant girth and height, length, girth, core diameter and weight of mother, primary and secondary rhizomes, number of primary and secondary rhizomes plant-1, yield plant-1 plot-1ha-1, incidence of rhizome rot, dry matter and oleoresin content. The genotypic coefficients of variability (GCV) were moderate for number of secondary rhizomes plant-1, weight of primary and secondary rhizomes and yield plant-1plot-1ha-1, whereas, the phenotypic coefficients of variability (PCV) were moderate for emergence, number of tillers and leaves plant-1, number of secondary rhizomes plant-1, weight of mother, primary and secondary rhizomes, yield plant-1 plot-1 ha-1, oleoresin content and incidence of rhizome rot. High heritability coupled with high and moderate genetic gain was observed for yield plot-1 ha-1 and weight of mother, primary and secondary rhizomes indicating the importance of these characters for selection. It indicated that these traits were amenable to selection. The overall assessment showed that there was wide variability among ginger genotypes which has important implication for breeding ginger for yield and quality attributes.